On the urgency of implementing Interest NACK into CCN: from the perspective of countering advanced interest flooding attacks. Issue 3 (1st May 2018) - Wang, Kai; Zhao, Yude; Liu, Shugang; Tong, Xiangrong
Abstract : Content centric networking (CCN) where content/named data as the first entity has become one of the most promising architectures for the future Internet. To achieve better security, the Interest NACKmechanism is introduced into CCN; however, it has not attracted enough attention and most of the CCN architectures do not embed Interest NACK until now. This study focuses on analysing the urgency of implementing Interest NACK into CCN, by designing a novel network threat named advanced interest flooding attack (AIFA) to attack CCN, which can not only exhaust the pending interest table (PIT) resource of each involved router just as normal interest flooding attack (IFA), but also keep each PIT entry unexpired until it finishes, making it harder to detect and more harmful when compared with the normal IFA. Specifically, the damage of AIFA on CCN architecture with and without Interest NACK is evaluated and analysed, compared with normal IFA, and then the urgency of implementing Interest NACK is highlighted.